Designing Novel Interfaces via Surface Functionalization of Short-Chain-Length Polyhydroxyalkanoates - S. Vigneswari; J. M. Chai; K. Shantini; K. Bhubalan; A. A. Amirul (Advances in Polymer Technology)
Polyhydroxyalkanoates (PHA), a microbial plastic has emerged as promising biomaterial owing to the broad range of mechanical properties. However, some studies revealed that PHA is hydrophobic and has no recognition site for cell attachment and this is often a limitation in tissue engineering aspects. Owing to this, the polymer is tailored accordingly in order to enhance the biocompatibility in vivo as well as to suit the intended application. Thus far, these surface modifications have led to PHA being widely used in various biomedical and pharmaceutical applications such as cardiac patches, wound management, nerve, bone, and cartilage repair. This review addresses the surface modification on biomedical applications focusing on short-chain-length PHA such as poly(3-hydroxybutyrate) [P(3HB)], poly(3-hydroxybutyrate-co-4-hydroxybutyrate) [P(3HB-co-4HB)] and poly(3-hydroxybutyrate-co-3-hydroxyvalerate) [P(3HB-co-3HV)].